Devices and Methods to Measure Female Sexual Arousal. Issue 4 (30th June 2015) - Kukkonen, Tuuli M.
Abstract Introduction Multiple methods and devices are available for the assessment of female sexual response, each with strengths and limitations that can impact interpretation of research results. As such, it is important to have an understanding of available methodologies and instruments. Aim To review recent literature on the measurement of female sexual response, and to describe the methods and devices, and their strengths and limitations. Methods A literature review was performed regarding methodology and instruments used to quantify female sexual response. Main Outcome Measures The description of currently available instruments and methods to quantify sexual response in women. Results Methodologies used to examine female sexual arousal employ a variety of stimuli and instruments to elicit and record sexual response. The variation in research designs across studies highlights the importance of understanding (i) how sexual response is elicited in studies; (ii) what kinds of experimental designs are available for assessing sexual psychophysiology; and (iii) the various types of instrumentation used to collect data. Conclusions The physiological and self‐reported measurement of female sexual response is crucial to our understanding of the mechanisms and factors involved with healthy sexual functioning. As such, it is important to understand the strengths and limitations associated with different stimuli, research designs, and instruments. Kukkonen TM. Devices and methods to measure female sexual arousal. Sex Med Rev 2015;3:225–244.